2013
DOI: 10.1007/s00167-013-2430-2
|View full text |Cite
|
Sign up to set email alerts
|

No difference in accuracy between pinless and conventional computer-assisted surgery in total knee arthroplasty

Abstract: In clinical routine, pinless CAS can comprise the advantages of CAS leaving the disadvantages aside. It reduces surgical time and avoids complications associated with the tracking pins of conventional CAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Navigation solely of the tibial cut would therefore be sufficient to securely restore leg axis, with concomitant enormous saving in additional time needed for navigation. Furthermore, this partial navigation technique can also be performed using a reduced, pinless, navigational workflow with high accuracy, which further reduces complications of pin placement [2]. There are several limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Navigation solely of the tibial cut would therefore be sufficient to securely restore leg axis, with concomitant enormous saving in additional time needed for navigation. Furthermore, this partial navigation technique can also be performed using a reduced, pinless, navigational workflow with high accuracy, which further reduces complications of pin placement [2]. There are several limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the hypotheses that: (1) the modified surgical technique with reduced navigation workflow approaches natural knee kinematics with lateral femoral rollback and tibial internal rotation with flexion; (2) alter condylar liftoff without midflexion instability; (3) significantly differ in femoral and tibial cuts, (4) restore the limb axis, and (5) there would be no differences in clinical outcome measures [Knee Society Scores (KSS), Western Ontario and McMaster Osteoarthritis Index (WOMAC)] prior to and at the latest follow-up between groups.…”
Section: Introductionmentioning
confidence: 99%
“…12 In addition, Chen et al have found that pinless navigation is an effective tool for reducing the proportion of outliers of normal alignment. 13 However, whether the satisfactory alignment or decreased proportion of outliers translated to any detectable differences in clinical outcomes was not previously described.…”
Section: Discussionmentioning
confidence: 99%
“…HKA hip-knee-ankle angle, mLDFA mechanical lateral distal femoral angle, mLPFA mechanical lateral proximal femoral angle, MediCAD_ AMA angle between the anatomical and the mechanical femoral axis determined with computer software, surgeon_AMA angle between the anatomical and the mechanical femoral axis determined by the surgeon by means of manual planning [1,14]. Because of the reported large anatomical differences in the AMA between 2° and 12.5° [7,21], we expected that preoperative measurement of the AMA would result in optimal coronal alignment perpendicular to the mechanical femoral axis [3,16,21].…”
Section: Discussionmentioning
confidence: 99%